En historisk ordbog og dens aner - Kvaran, Guðrún (Nordiske Studier i Leksikografi, 1995)
The subject of this paper is a historical dictionary being worked on at present at the Institute of Lexicography in Reykjavik, and the value of alder dictionaries as sources for that work. The problems of excerpting from alder material, especially from early periods where sources can be insufficient or incomplete, inevitably makes alder dictionaries a prominent source for historical dictionaries, no matter how deficient or incomplete they are. An account is given of the major Icelandic dictionaries, both in manuscript and in print, from the l 7th to the early l 9th century.